2003
DOI: 10.1016/s0012-1606(02)00115-x
|View full text |Cite
|
Sign up to set email alerts
|

BMP receptor 1b is required for axon guidance and cell survival in the developing retina

Abstract: Previous work has documented the importance of BMPs in eye development. Loss-of-function studies in mice, with targeted deletions in either the Bmp7 or Bmp4 genes, have shown that these molecules are critical for early eye development. On the basis of the asymmetry in the dorsal-ventral expression patterns of several members of this family, it has been proposed that these molecules are critical for some aspect of dorsal-ventral patterning in the eye; however, it has been difficult to test this hypothesis becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 47 publications
5
85
0
Order By: Relevance
“…It was previously confirmed that BMP7 may promote DNA synthesis in brain cells cultured in vitro and simultaneously promote the dendrite growth of sympathetic neurons cultured in vitro (12). In rats without BMP type I receptors, the expression of netrin, a nerve growth factor that induces axon growth, is inhibited (13). Therefore, the activation of BMP signal transduction plays an important role in cell proliferation and neural regeneration.…”
Section: Discussionmentioning
confidence: 92%
“…It was previously confirmed that BMP7 may promote DNA synthesis in brain cells cultured in vitro and simultaneously promote the dendrite growth of sympathetic neurons cultured in vitro (12). In rats without BMP type I receptors, the expression of netrin, a nerve growth factor that induces axon growth, is inhibited (13). Therefore, the activation of BMP signal transduction plays an important role in cell proliferation and neural regeneration.…”
Section: Discussionmentioning
confidence: 92%
“…The same appears to apply to other stress-induced p53 target genes, as revealed by comparative expression analysis in wild-type and p53-deficient mice, demonstrating both p53-dependent and p53-independent expression of Bax, Fas, Killer, and Mdm2 in different cell types of adult mice. 54,55 Perp and its PMP22 relatives: possible mechanisms of action During embryonic development, several important regulators, such as members of the family of Bone Morphogenetic proteins, have both pro-and antiapoptotic effects, depending on the cellular context (see for example Liu et al 56 and Israsena and Kessler 57 ). However, the molecular mechanisms underlying these contrary effects are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…They also regulate the differentiation and survival of retinal neurons (7)(8)(9)(10)(11). Because of the BMP pathway's importance during retina development and in stem cell biology, we wanted to examine its role in inducing and regulating retina regeneration.…”
mentioning
confidence: 99%